WYZWANIA POLITYKI MIGRACYJNEJ FEDERACJI ROSYJSKIEJ – STUDIUM PRAWNE, SOCJOLOGICZNE I GEOPOLITYCZNE (wersja poprawiona) - Wojnicz, Piotr (Civitas et Lex, 2015)
Migration is a mass phenomenon of our time, a permanent phenomenon which takes many forms, affects all continents and all countries. This phenomenon is one of the most important social and international issues of the modern world. In this context, the Russian Federation is not free from problems arising from migration processes. Migration policy of the Russian Federation is a very important part of that country’s geopolitical game. Location Russia between the European Union and China creates considerable scope to influence the shape of migration processes not only regional but also global. Russia has become a country of immigration. There are two very important aspects in the migration policy of Russia: the internal and external aspects. The internal aspect relates to such phenomena as the fight against the demographic crisis and related deficits in the labor market, national and religious revival of ethnic groups living in Russia, the low level of social integration of immigrants. In terms of external migration policy is treated as an instrument of pressure on the countries of the former Soviet Union, a way of shaping relations with China and the element of national security. Russian migration policy is an active instrument for solving problems within the country, as well as a very important foreign policy wizard. Pejorative side of this policy is that it is planned from above, without taking into account the needs and nature of various Russian regions.